2017
DOI: 10.1039/c7nr06526d
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenated MoS2 QD-TiO2 heterojunction mediated efficient solar hydrogen production

Abstract: Herein, we report the development of a hydrogenated MoS QD-TiO (HMT) heterojunction as an efficient photocatalytic system via a one-pot hydrothermal reaction followed by hydrogenation. This synthetic strategy facilitates the formation of MoS QDs with an enhanced band gap and a proper heterojunction between them and TiO, which accelerates charge transfer process. Hydrogenation leads to oxygen vacancies in TiO, enhancing the visible light absorption capacity through narrowing its band gap, and sulfur vacancies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…Furthermore, it also exhibits a strong affinity for H + in reaction system. [32][33][34] Therefore, it can be seen that the hydrogen evolution performance of MoS 2based photocatalysts is mainly restricted by active edge and the specific surface of MoS 2 . The different morphologies of MoS 2 materials, such as quantum dots, nanosheets, nanoparticles and monolayer or few layers, have been designed and prepared by the previous report.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it also exhibits a strong affinity for H + in reaction system. [32][33][34] Therefore, it can be seen that the hydrogen evolution performance of MoS 2based photocatalysts is mainly restricted by active edge and the specific surface of MoS 2 . The different morphologies of MoS 2 materials, such as quantum dots, nanosheets, nanoparticles and monolayer or few layers, have been designed and prepared by the previous report.…”
Section: Discussionmentioning
confidence: 99%
“…Because abundant active sites can be provided on the exposed edge of MoS 2 , attributing to the existence of unsaturated S atoms. Furthermore, it also exhibits a strong affinity for H + in reaction system . Therefore, it can be seen that the hydrogen evolution performance of MoS 2 ‐based photocatalysts is mainly restricted by active edge and the specific surface of MoS 2 .…”
Section: Methodsmentioning
confidence: 99%
“…87‐1526) . Restricted by the lower amount and crystallinity, the diffraction peaks of the MoS 2 QDs could be hardly observed . It is interesting that the diffraction peaks of B‐TiO 2 /g‐C 3 N 4 /MoS 2 are similar to that of B‐TiO 2 /g‐C 3 N 4 and TiO 2 /g‐C 3 N 4 , which manifests that the Ti 3+ self‐doping would hardly influence the crystal structure of TiO 2 , and the samples exhibit high stability during the process of the deposition and reduction, including the g‐C 3 N 4 , which would be an advantage for continuous photocatalysis.…”
Section: Resultsmentioning
confidence: 96%
“…In addition, the small size effect of the MoS 2 QDs can increase the diffusion of photogenerated carriers toward the increased HER, and such modification has been reported by previous literature. For example, Saha et al have reported the MoS 2 QDs modified TiO 2 heterojunction with efficient solar HER; Lee et al have fabricated the MoS 2 QDs decorated Bi 2 S 3 with remarkable hydrogen evolution; Wang et al have reported the MoS 2 QDs@TiO 2 nanotube arrays to enhance the solar hydrogen evolution; and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Self-doping, particularly defects from oxygen vacancies, is alwaysa dvantageous for the improvement of properties compared with conventional doping systems, in which the introduction of impurities, that is, doped elements, may cause a reduction in catalytic activity. [2,14] Oxygen defects that induce improvementsi nt he thermo- [15] andp hotocatalytic [16] activity of ZnO have been reported. However,i nt hese samples the extent of oxygen deficiencies is very limited owing to the instabilityo fo xygen vacancies under ambient conditions.…”
Section: Introductionmentioning
confidence: 99%